Uji Karakteristik Sediaan Salep Ekstrak Etanol Daun Sambung Nyawa (Gynura Procumbens (Lour.) Merr.) - Novycha Auliafendri; Agnes Kris Darna Ningsi Gee (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
The leaves of the lifeless tree (Gynura procumbens (Lour.) Merr.) have been widely used as traditional medicine and show that they can treat various diseases and infections with simple processing. However, the use of life-giving leaves as an ointment to treat wounds is very rare. The aim of this research was to produce ointment and assess the characteristics of ointments made with ethanol extract of sambungjiwa leaves. The ointment used in this research was made with ethanol extract of sambungjiwa leaves, adeps lanae, vaseline album, distilled water. Data was observed descriptively and using qualitative research methods. This study used three ointment concentrations, namely 5%, 10%, 15%, tested three times for each characteristic evaluation (organoleptic test, pH test, spreadability test, homogeneity test). The results of the research showed that the ethanol extract of the succinct leaves can be formulated as an ointment and the evaluation of the characteristics of the ointment showed that in the organoleptic test it appeared to be green in color with a semi-solid form and had a distinctive odor of the ethanol extract of the succinct leaves; the pH test shows a pH value of 5; the spreading power test shows a spreading power value of 5; and the homogeneity test showed that there were no coarse or fine grains and no color change at the beginning or end so that from the results of the characteristic test it could be concluded that the ethanol extract ointment preparation of sambungjiwa leaves met the standard requirements of the ointment characteristic test.